ILLUSIONS OF CLIMATE SCIENCE. - KININMOTH, WILLIAM (Quadrant Magazine, 2008)
The author offers views on the Australian government's efforts to prevent climate change. He believes that a widely accepted conviction that dangerous climate change is pending is required before the community will support the government's strategy to shut down fossil-fuel-dependent industries and abandon their energy-dependent activities. He comments on the use of computer models to make projections about human-caused global warming. He also predicts the failure of carbon dioxide emission reduction efforts.